2021
DOI: 10.1161/jaha.120.021375
|View full text |Cite
|
Sign up to set email alerts
|

Distinction in Prevalence of Atherosclerotic Embolic Sources in Cryptogenic Stroke With Cancer Status

Abstract: Background Cerebrovascular diseases are common comorbidities in patients with cancer. Although active cancer causes ischemic stroke by multiple pathological conditions, including thromboembolism attributable to Trousseau syndrome, the relationship between stroke and inactive cancer is poorly known. The aim of this study was to elucidate the different underlying pathogeneses of cryptogenic stroke in active and inactive patients with cancer, with detailed investigation by transesophageal echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…По данным регистра CHALLENGE ESUS/CS (пациенты с криптогенным инсультом и ЧП-ЭхоКГ), активное ЗНО выявлено в 6,1% случаев, неактивный рак -в 7,5% случаев. Активный рак оказался ассоциирован с множественными инфарктами, тогда как неактивный -с наличием атеросклеротических источников эмболии [68].…”
Section: рак-ассоциированный инсультunclassified
“…По данным регистра CHALLENGE ESUS/CS (пациенты с криптогенным инсультом и ЧП-ЭхоКГ), активное ЗНО выявлено в 6,1% случаев, неактивный рак -в 7,5% случаев. Активный рак оказался ассоциирован с множественными инфарктами, тогда как неактивный -с наличием атеросклеротических источников эмболии [68].…”
Section: рак-ассоциированный инсультunclassified
“… 17 Thus, many studies sought to identify the typical characteristics of cancer-associated, presumably paraneoplastic stroke in comparison to ischemic stroke not associated with cancer. These characteristics have been found to comprise the simultaneous involvement of two or more vascular territories, 18 20 elevated lactate dehydrogenase (LDH), 6 elevated D-dimers as marker for hypercoagulability, 19 22 as well as a systemic inflammatory response with increased C-reactive protein (CRP) 18 , 22 24 and relative granulocytosis. 6 , 20 All these laboratory markers are also elevated in cancer patients compared to controls; 25 , 26 however, CRP and D-dimer elevations are more pronounced in patients with cancer and concomitant ischemic stroke compared to patients with cancer only.…”
Section: Introductionmentioning
confidence: 99%
“…A postmortem-based study reported that about 14.6% of non-CNS cancer cases showed cerebrovascular disease (CVD) (Graus et al, 1985 ). Moreover, embolic strokes are the most common cause of strokes in patients with cancer, possibly due to intravascular coagulopathy (Cestari et al, 2004 ); patients with active cancer show multiple infarcts (Kikuno et al, 2021 ). Gliomas account for 60% of ischemic strokes secondary to primary brain tumors, whereby complications due to surgery and radiotherapy form the majority (Kreisl et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A postmortem-based study reported that about 14.6% of non-CNS cancer cases showed cerebrovascular disease (CVD) (Graus et al, 1985). Moreover, embolic strokes are the most common cause of strokes in patients with cancer, possibly due to intravascular coagulopathy (Cestari et al, 2004); patients with active cancer show multiple infarcts (Kikuno et al, 2021). Gliomas account Abbreviations: TCGA, The cancer genome atlas; CGGA, Chinese glioma genome atlas; LGG, Lower-grade gliomas; GBM, Glioblastomas; RBP, RNA-binding protein; LASSO, Least absolute shrinkage and selection operator; GO, Gene ontology; GSEA, Gene set enrichment analysis; IDH, Isocitrate dehydrogenases; MGMT, O -methylguanine-DNA methyltransferase; IS, Ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%